Comparative analyses of gut microbiota reveal ammonia detoxification and nitrogen assimilation in Cyprinus carpio var. specularis - Talwar, Chandni; Nagar, Shekhar; Negi, Ram Krishan (Folia microbiologica, 2024)
The complex niche of fish gut is often characterized by the associated microorganisms that have implications in fish gut-health nexus. Although efforts to distinguish the microbial communities have highlighted their disparate structure along the gut length, remarkably little information is available about their distinct structural and functional profiles in different gut compartments in different fish species. Here, we performed comparative taxonomic and predictive functional analyses of the foregut and hindgut microbiota in an omnivorous freshwater fish species, Cyprinus carpio var. specularis, commonly known as mirror carp. Our analyses showed that the hindgut microbiota could be distinguished from foregut based on the abundance of ammonia-oxidizing, denitrifying, and nitrogen-fixing commensals of families such as Rhodospirillaceae, Oxalobacteraceae, Nitrosomonadaceae, and Nitrospiraceae. Functionally, unique metabolic pathways such as degradation of lignin, 2-nitrobenzoate, vanillin, vanillate, and toluene predicted within hindgut also hinted at the ability of hindgut microbiota for assimilation of nitrogen and detoxification of ammonia. The study highlights a major role of hindgut microbiota in assimilating nitrogen, which remains to be one of the limiting nutrients within the gut of mirror carp.
Keywords: Animals; Ammonia; Metabolic Networks and Pathways; Nitrogen; Gastrointestinal Microbiome; kapři; RNA, Ribosomal, 16S; metabolické sítě a dráhy; gastrointestinální trakt; Inactivation, Metabolic; metabolická inaktivace; Phylogeny; Bacteria; střevní mikroflóra; Carps; zvířata; Gastrointestinal Tract; fylogeneze; amoniak; RNA ribozomální 16S; dusík